Shakespeare and the Digital World : Redefining Scholarship and Practice - Carson, Christie; Kirwan, Peter (Cambridge : Cambridge University Press, 2014)
Due to the unique cultural capital of his works, Shakespeare has long been the test subject for new methods and digital advances in arts scholarship. Shakespeare sits at the forefront of the digital humanities - in archiving, teaching, performance and editing - impacting on scholars, theatres and professional organisations alike. The pace at which new technologies have developed is unprecedented (and the pressure to keep up is only growing). This book offers seventeen new essays that assess the opportunities and pitfalls presented by the twenty-first century for the ongoing exploration of Shakespeare. Through contributions from a broad range of scholars and practitioners, including case studies from those working in the field, the collection engages with the impact of the digital revolution on Shakespeare studies. By assessing and mediating this sometimes controversial digital technology, the book is relevant to those interested in the digital humanities as well as to Shakespeare scholars and enthusiasts.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Literature and technology